The pre-oral phase of swallowing and its disorders among people with severe intellectual disability - Chilińska-Pułkowska, Alicja; Kaczorowska-Bray, Katarzyna (Logopedia Silesiana, 2020)
The present paper aims, on the basis of the literature on the subject and the surveys carried out among parents/caregivers, at defining the pre-oral phase of swallowing and its course in people with severe intellectual disability. The definitions are presented, the course of this phase and the determinants influencing its disorders are characterized. The paper also indicates the possibility of improving feeding by changing behaviour in its earliest pre-oral phase. In order to collect data to assess the most important behaviours used by caregivers when initiating feeding, surveys were conducted among the caregivers of Rehabilitation, Educational and Pedagogic Center in Pruszcz Gdański. The research is based on the group of people with a certificate of severe disability, with various dysfunctions concerning eating.